INTRODUKSI HIJAUAN MAKANAN TERNAK SAPI DI MINAHASA SELATAN - Femi H. Elly; P. O. V. Waleleng; Ingriet D. R. Lumenta; F. N. S. Oroh (Udayana University)
The role of cattle as a source of food for the community in the form of meat. The problem of cattle population in North Sulawesi tend to decrease. The slow growth of the cattle population is determined by external factors such as feed. Based on these ideas, has made the study of food forage introduction of cattle in South Minahasa. Premise that cattle is a commodity that the government should pursue policies relating to the availability of forage continuously. Forage fodder is a major food or feed for livestock and is the basis of life in the animal husbandry development effort. To increase the productivity of livestock, one of the important factors that must be considered is the provision of good quality feed year round and enough quantity. In response to the government policy in South Minahasa has made the development of cattle forage food. In conclusion, the introduction of green fodder is very beneficial to farmers in the development of cattle ranchers. Based on the introduction of forage necessary assistance to livestock farmers for forage management.